The synthesis and crystal structure of Cbz-[(1R,2S)-ACPC]3-OH: A tripeptide derived from the β-amino acid (1R,2S)-cispentacin - Davies, S; Siddall, E; Thompson, A; Thomson, J (Springer New York LLC, 2014)
Crystals of the tripeptide Cbz-[(1R,2S)-ACPC]3-OH 4, derived from the β-amino acid (1R,2S)-2-aminocyclopentanecarboxylic acid, were synthesised and studied by X-ray diffraction. Tripeptide 4 crystallizes in the orthorhombic space group P 2 1 2 1 2 1 with cell parameters of a = 7.8957(1) Å, b = 12.9289(2) Å, c = 24.7850(4) Å, V = 2530.12(6) Å3 and Z = 4. Adjacent molecules are linked by a series of N-H···O=C and O- H···O=C hydrogen bonds to form a double tape-like arrangement. Graphical Abstract: The structure of a tripeptide derived from the β-amino acid (1R,2S)-2-aminocyclopentanecarboxylic acid has been analysed by X-ray diffraction.[Figure not available: see fulltext.] © 2014 Springer Science+Business Media New York.